Demography of smallholder agricultural women and youth enterprises and their association with the cultivation of the tomato (Solanum Lycopersicum) vegetable crop - Nesamvuni, Azwihangwisi E.; Tshikolomo, Khathutshelo; Mpandeli, Ndivhudzannyi S.; de Bruyn, Melanie; Hlophe-Ginindza, Samkelisiwe; van Niekerk, Johan (Technium Social Sciences Journal, 2022)
The study was conducted at the Madimbo corridor and upper Mutale valley smallholder irrigation schemes. The purpose of the study was to characterize smallholder agricultural women and youth entrepreneurs (SHAW-YE). A semi-structured household questionnaire together with facilitation was used to survey a sample, purposively focusing on Smallholder Agriculture Women and Youth Enterprises (SHAW-YE). The sample was comprised of 294 respondents with sub-samples of respondents selected through gender category, age category, and gender by age category. The study revealed that the SHAW-YE are characterized by small land areas under cultivation. There were some associations between age, education, and income of SHAW-YE with their capacity to produce tomatoes. Participation of women was 48.4% compared to 20% of men in the winter production of tomatoes. Production participation by SHAW-YE farmers for summer revealed that women were participating at 9.7% compared with 13.3% for men. The participation of SHAW-YE around the ages of 36-59-year was at 52.9% while that for ages >60-year was at 51.5%. The main source of variation may be the level of experience that the said age group of SHAW-YE may have in the production of tomatoes compared to 29.6% of 18–35-year participants. About 61.7% of SHAW-YE were at the level of Adult Basic Education & Training (ABET). About 45.8% of the SHAW-YE earned less than R5000.00 compared with 50.7% earning more than R5000.00. Market channels and access should be promoted for SHAW-YE to enable the throughput of tomatoes to not only informal but also fresh produce and retail markets.